Comparison of NiTi orthodontic archwires and a determination of the charasteristic properties - Ferčec, Janko (Materiali in tehnologije, 2014)
The aim of this paper was to analyse the characteristic properties of six different, commercially available nickel-titaniumorthodontic wires with a diameter of 0.305 mm (0.014"). The characteristic properties were determined by usingsemi-quantitative EDX analyses, DSC analyses for a determination of the phase temperatures, and a tensile test to obtain themechanical properties of the wires. The investigation of the chemical composition showed an equiatomic NiTi alloy. Analysesof phase temperatures showed that the nickel-titanium orthodontic wires were, in an austenitic microstructure, exhibiting asuperelastic effect in the oral environment. The uniaxial tensile stressstrain curves showed different values for the beginningand the end of the transformation range during the loading.
Keywords: shape-memory alloy; tensile test; nikljeve zlitine; phase transformation; thermal analysis; titanove zlitine; zlitina s spominom oblike; fazna transformacija; termična analiza; natezni preizkus